2018
DOI: 10.1111/plb.12930
|View full text |Cite
|
Sign up to set email alerts
|

Can obligate apomixis and more stable reproductive assurance explain the distributional successes of asexual triploids in Hieracium alpinum (Asteraceae)?

Abstract: Although reproductive assurance has been suggested to be one of the most important factors shaping the differential distributional patterns between sexuals and asexuals (geographic parthenogenesis), it has only rarely been studied in natural populations of vascular plants with autonomous apomixis. Moreover, there are almost no data concerning the putative relationship between the level of apomictic versus sexual plant reproduction on one hand, and reproductive assurance on the other. We assessed the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 48 publications
2
25
1
Order By: Relevance
“…Comprehensive population genetic studies on GP scenarios, however, either did not observe the respective genetic pattern (e.g., Cosendai et al., 2013) or found the colonization history and decline of genetic diversity in marginal sexual populations as less relevant for the GP pattern (e.g., Nardi et al., 2020). On the contrary, apomictic lineages can benefit from uniparental reproduction either via pollen‐independent (autonomous) apomixis (Mráz et al., 2018) or via pseudogamy and self‐compatibility (Hörandl, 2010) without negative effects of inbreeding. However, little is known about the effects of breeding systems, inbreeding, and fitness of sexual species in geographical parthenogenesis scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive population genetic studies on GP scenarios, however, either did not observe the respective genetic pattern (e.g., Cosendai et al., 2013) or found the colonization history and decline of genetic diversity in marginal sexual populations as less relevant for the GP pattern (e.g., Nardi et al., 2020). On the contrary, apomictic lineages can benefit from uniparental reproduction either via pollen‐independent (autonomous) apomixis (Mráz et al., 2018) or via pseudogamy and self‐compatibility (Hörandl, 2010) without negative effects of inbreeding. However, little is known about the effects of breeding systems, inbreeding, and fitness of sexual species in geographical parthenogenesis scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…is expressed solely at the polyploid level. This pattern has recently been found in large‐scale flow cytometric studies of seed progeny of diploid and polyploid taxa (Mráz & Zdvořák, ; Mráz & al., ). In the same line of evidence, published (Mráz & Paule, ) and unpublished data (Pinc & al., unpub.)…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, apomicts of Pilosella officinarum showed marginally higher fecundity when compared to sexuals (Sailer et al., 2020). By contrast, no differences in seed set were found between two reproductive forms in Antennaria parlinii (Asteraceae, O’Connell & Eckert, 1999) and Hieracium alpinum (Asteraceae, Mráz et al., 2019). In the two latter studies, allopatrically distributed asexual and sexual populations were studied and found high level of between‐population heterogeneity in seed sets within both apomicts and sexuals.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, nonautonomous seed formation, decreased seed sets and residual sexuality are likely the most important factors, why GP patterns are substantially rarer in pseudogamous apomicts when compared to autonomous apomicts (Hörandl et al., 2008). Surprisingly, given its ecological importance, the advantage of uniparental reproduction has rarely been quantified in autonomous apomicts (Mráz et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation